The Influence Of Rewards And Punishment On The Performance Of Astra Credit Company ( ACC ) Bengkulu Office Employees - Oktian, Bima Dwi; Afriani , Sulisti; Astuty , Kamelia (Universitas Dehasen Bengkulu, 2024)
One of the strategies that must be implemented by the company is to increase the company's competitiveness, quality service to consumers and the competency of the company's human resources. Because of this, human resources are still the main focus for a company to continue to exist in this era of globalization. HR is a very important thing in an organization, because the success of an organization really depends on the quality and performance of the individuals in the organization. The purpose of this research is to determine the effect of rewards and punishment on employee performance at the Astra Credit Company ( ACC) Bengkulu office. In this research, the type of researcher using a quantitative research approach method is used to research a certain population or sample. The population in this study was all employees of the Astra Credit Company (ACC) Bengkulu office, totaling 50 employees.The results of the multiple linear regression analysis are Y = 10.611 + 0.390 X1 + 0.374 X2 +e. From the results of calculations using SPSS it can be seen that the coefficient of determination value of R square is 0.666. From the results of calculations using SPSS it can be seen that the coefficient of determination value of R square is 0.666. This means that the reward value (X1) and punishment value (X2) influence employee performance (Y) by 66.6% while the remaining 33.4% is influenced by other variables not examined in this research.